Hypokalaemic myopathy associated with iatrogenic hypercorticism in a cat - Annamaria Tiozzo Ambrosi; Giorgia Lovato; Laura Pintore; Carolina Callegari; Alice Tamborini (Journal of Feline Medicine and Surgery Open Reports)
Case summary A 12-year-old castrated male domestic shorthair cat was referred for investigation of lethargy, hindlimb weakness with plantigrade stance and ventroflexion of the neck. The cat was fed a balanced diet and had received methylprednisolone acetate at a dose of 20 mg intramuscularly every 6 months for 6 years. On blood work, severe hypokalaemia and marked elevation of muscle enzymes were noticeable. The findings were suggestive of hypokalaemic myopathy. Urine fractional excretion of potassium (FE k ) was moderately high (9.04%), and serum aldosterone was below the reference interval. An adrenocorticotropic hormone (ACTH) stimulation test was compatible with adrenal suppression. Upon hospitalisation, the patient was given intravenous (IV) Ringer lactate solution supplemented with potassium chloride and oral potassium citrate. The serum potassium concentration normalised by the fifth day of hospitalisation; therefore, IV potassium supplementation was suspended. The cat was discharged with oral potassium and the dose was gradually reduced over time. After 4 months, the cat was clinically normal; the serum potassium concentration remained within the normal range and the adrenal glands showed some response to ACTH stimulation. Potassium supplementation was therefore discontinued. One month later, the serum potassium concentration was still within normal limits and at the time of writing (7 months after presentation), no clinical signs had reoccurred. Relevance and novel information This report describes a case of hypokalaemic myopathy associated with iatrogenic hypercorticism in a cat. This condition was successfully treated with supplementation of potassium and a complete clinical remission was achieved within 4 months.